2018
DOI: 10.1088/1748-9326/aab9e0
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of the Three Gorges Dam on the thermal dynamics of the Yangtze River

Abstract: This study examines the impact of the world's largest dam, the Three Gorges Dam (TGD), on the thermal dynamics of the Yangtze River (China). The analysis uses long-term observations of river water temperature (RWT) in four stations and reconstructs the RWT that would have occurred in absence of the TGD. Relative to pre-TGD conditions, RWT consistently warmed in the region due to air temperature (AT) increase. In addition, the analysis demonstrates that the TGD significantly affected RWT in the downstream reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 74 publications
0
51
0
Order By: Relevance
“…With respect to the pre-TGD condition, the post-TGD implies RWT expanded by 1.71 o C and 0.06 o C in cold and warm seasons, separately. 81 By methods for the air2stream demonstrate, 82 reproduced the potential RWT exclusively because of changes in the meteorological compelling (for example AT) and stream Q. Along these lines, we were likewise ready to measure alteration(s) that can be ascribed to the nearness of huge scale human mediations, basically spoken to by the TGD, in this way contrasting the recreated and watched RWT in the post-TGD period.…”
Section: Discussionmentioning
confidence: 90%
“…With respect to the pre-TGD condition, the post-TGD implies RWT expanded by 1.71 o C and 0.06 o C in cold and warm seasons, separately. 81 By methods for the air2stream demonstrate, 82 reproduced the potential RWT exclusively because of changes in the meteorological compelling (for example AT) and stream Q. Along these lines, we were likewise ready to measure alteration(s) that can be ascribed to the nearness of huge scale human mediations, basically spoken to by the TGD, in this way contrasting the recreated and watched RWT in the post-TGD period.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, the potential effects of human activities (particularly for Yichang station) on the water‐air temperature dependence could also be related to the changes in dependence structures, such as water consumption, water supply regulations, irrigation, dams, industrialization, and impoundments and wastewater inputs, or by groundwater inflows (Chen et al, ; Erickson & Stefan, ; O'Driscoll & DeWalle, ). For the stations downstream of the TGD, existing studies also reported that the variation in water‐air temperature dependence structure could be partially attributed to the TGD's operation (e.g., Cai et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The Yangtze River, the largest river in China, has attracted considerable attention from different research fields, such as social economy, ecology, hydrology, and climatology, especially after the world's largest and possibly most controversial dam began operation in 2003 (Chen et al, ; Lai et al, ). In past decades, a large number of studies have examined the flow regime change, discharge trend, extreme flood, and drought events, changes in local weather and climate, and aquatic ecosystem variation over the Yangtze River under the effect of the Three Gorges Dam (TGD) (Cai et al, ; Chen et al, ; Guo et al, ; Lai et al, ; Li et al, ; Liu et al, ; Nakayama & Shankman, ; Zhang et al, ). However, little knowledge has been reported regarding the relationships between water temperature and both air temperature and river discharge over the Yangtze River, although a few studies have addressed the variation in water temperature itself and its implications to aquatic ecology (Guo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, temperature is known to determine physiology and metabolic rates of organisms (Catenazzi & Kupferberg, 2018;Tao, Kennard, Jia, & Chen, 2018), fecundity (Farrell, 2009), recruitment and mortality (Catenazzi & Kupferberg, 2018;Coulter, Sepúlveda, Troy, & Höök, 2016;Gaufin & Hern, 1971), and influence species distribution (Howell, 2017;Mee, Robins, & Post, 2016). Regulated rivers around the world generally exhibit altered temperature magnitudes, rates of change, and timing characteristics (Cai et al, 2018;Casado, Hannah, Peiry, & Campo, 2013) compared with preregulation conditions (Maheu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%